Gypsum and organic materials improved soil quality and crop production in saline-alkali on the loess plateau of China - Tian, Ye; Jiang, Wenting; Chen, Guoliang; Wang, Xiukang; Li, Tingting (Frontiers in Environmental Science, 2024)
Arable soil and crop productivity are severely affected by salinization. Therefore, soil amendments are an important measure for improving saline-alkali soil for agricultural development. Desulfurized gypsum is a common soil amendment that has been used repeatedly alongside organic materials to improve the biological, physical, and chemical properties of saline soil. This study takes the typical saline-alkali farmland soil in Yulin as the research object, and five treatments were established: a blank treatment (CK), a single application 2.5 t ha-1 of desulfurized gypsum (T), 2.5 t ha-1 of desulfurized gypsum and 1.5 t ha-1 of green manure (TL), application 2.5 t ha-1 of desulfurized gypsum and 1.5 t ha-1 of straw (TS), and 2.5 t ha-1 of desulfurized gypsum and 1.5 t ha-1 of organic fertilizer (TV). The results show that the TV treatment achieved a significant improvement in soil nutrients, organic carbon, enzyme activity, and maize yield. In 2022 (2023), the compared of organic matter, TN, TP, TK, AP, and AK increased significantly compared with the CK treatment when the TV treatment was applied. Soil phosphatase activity (SPA), soil urease activity (SUA) and soil sucrase activity (SSA) significantly higher in the TV treatment compared with the other treatments and increased significantly over the two-year period. Furthermore, soil organic carbon (SOC), easily oxidizable organic carbon (EOC), dissolved organic carbon (DOC) and microbial biomass carbon (MBC) also significantly increased with the 2022 and 2023 TV treatments. Correlation analysis revealed a positive relationship between maize yield and soil nutrients, organic carbon, and enzyme activity (P<0.05). Thus, the TV treatment was determined to be the optimal treatment for soil improvement. This conclusion was supported by analyses performed using membership function analysis, gray correlation analysis, and entropy TOPSIS model evaluation. Therefore, this method increases soil quality, improves soil fertility, achieves high maize yields, and provides a scientific basis for enhancing and utilizing saline-alkali soil in the Loess Plateau.